UPAYA GURU MENGATASI PROBLEMATIKA PEMBELAJARAN SKI BERBASIS AL QUR’AN DI MTS AL URWATUL WUTSQO JOMBANG - Nurul Indana (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2019)
The history of Islamic Culture is one of the important lessons to be learned especially for Muslims as an effort to shape the character and personality of the people from the journey of a character or previous generation. In general, in reality the History of Islamic Culture is less desirable. Historical subjects are underestimated or only considered as supplementary lessons both by students and teachers. But there are different things at MTs Al Urwatul Wutsqo Jombang. The MTs makes an innovation, namely the Qur'an-based SKI. The results of this study found that problems: problems with learning resources that are incomplete, lack of understanding of methods, lack of media to meet learning objectives, student problems before and during learning, evaluation values are substandard. Teacher's efforts: learning resources are overcome by the internet as a complementary resource, methods are overcome by other methods prepared by the teacher, media is overcome with other media that are easy to find, students are overcome with some common things, evaluations are overcome with remedial programs.